2018
DOI: 10.1007/s40264-018-0661-3
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events to Food Supplements Containing Red Yeast Rice: Comparative Analysis of FAERS and CAERS Reporting Systems

Abstract: Notwithstanding recognized limitations, these findings strengthen the importance of exploring multiple databases in safety assessment of RYR products, which should be monitored by clinicians for muscular and hepatic safety, and call for urgent review by policymakers to harmonize their regulatory status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…The present study reveals the most reported ADRs due to the use of RYR supplements to Lareb. It can be noted that the profile of reported ADRs to RYR of the present study is in line with previous studies, 14–16 ] with musculoskeletal and gastrointestinal, as the most frequently reported adverse effects (AEs). Although similar studies have been published before, these supplements are being used on a large scale and new cases of AEs due to these supplements arise.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study reveals the most reported ADRs due to the use of RYR supplements to Lareb. It can be noted that the profile of reported ADRs to RYR of the present study is in line with previous studies, 14–16 ] with musculoskeletal and gastrointestinal, as the most frequently reported adverse effects (AEs). Although similar studies have been published before, these supplements are being used on a large scale and new cases of AEs due to these supplements arise.…”
Section: Discussionsupporting
confidence: 91%
“…This might explain the 3 cases of liver injury identified by the present study. In addition to the 3 cases reported by our study, multiple other cases of RYR‐induced liver toxicity have been documented 14,15 Three individual cases of severe hepatitis due to RYR were published previously, highlighting that, despite the low incidence of liver injury, the use of RYR supplements might have serious health consequences 32–34 The exact mechanism by which RYR causes hepatotoxicity is not well understood yet. However, it is expected that liver injury by RYR supplements may be attributed to the presence of lovastatin, as liver injuries are also among the most reported side effects of statin users 1,35–37 Similar to the musculoskeletal adverse effects, mitochondrial dysfunction is proposed to play a major role in the observed liver injury by statins 38,39 …”
Section: Discussionmentioning
confidence: 54%
“…Moreover, three important points need to be taken into consideration: (1) Recognizing that FRMR contains a statin-like compound; (2) carefully recommending FRMR to statin-intolerant patients with a history of myositis or myopathy; (3) Documenting all alternative medicines, such as FRMR, taken by patients, in order to weigh the benefit-to-risk of co-administration of other drugs (Polsani et al, 2008). Overall, the real-world vigilance should be strengthened at different levels, including consumers, clinicians and policy-makers to promote the proper use and harmonize the regulatory status of FRMR (Raschi et al, 2018;Farkouh and Baumgärtel, 2019).…”
Section: Safety Evaluation Of Frmrmentioning
confidence: 99%
“…Adverse effects associated with red yeast rice that are repeatedly reported, include symptomatic myopathy,30–32 gastrointestinal symptoms,31,33 and elevated levels of hepatic enzymes indicative for liver injury 3133. Recently, exacerbation of myasthenia gravis and development of erectile dysfunction have also been attributed to red yeast rice intake in two individual cases 34,35…”
Section: Safety Profile Of Red Yeast Ricementioning
confidence: 99%